Conductive Atomic Force Microscopy : Applied and Modeled - Emmons, Samuel (My University, 2012)
An Atomic Force Microscope, or AFM, is a research instrument in the Scanning Probe Microscope, or SPM, family of instruments. An SPM is any device which probes or examines certain characteristics of a sample surface being studied. Atomic Force Microscopes use a very sharp tip attached to a lever arm (cantilever) to probe a range of sample characteristics at the micro and nano-scale. The most basic use of the AFM is to generate an image of sample topography, i.e. to see what the surface looks like. This is typically done in two modes, each of which maintains a prescribed condition on the photo-detector. One of the two, called Contact Mode, maintains a constant cantilever deflection, meaning it keeps the reflected laser beam at the same spot on the photo-detector. While AFM topography can provide quantitative sample data, Conductive AFM (CAFM) provides only qualitative data. This study used tools to develop models and methods to approach CAFM more quantitatively.
Color poster with text, diagrams, images, and graphs.
Keywords: Atomic force microscopy; Qualitative research; Quantitative research; Stereology; Posters